2020
DOI: 10.1177/0145561320933390
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Congenital Supernumerary Nostril in an Adult Patient

Abstract: The supernumerary nostril is a congenital accessory nostril, which is considered to be one of the rarest congenital nasal anomalies with an unknown etiology. We present the first case of a supernumerary nostril in an adult Saudi patient, which is the first such isolated case to be reported among the Middle Eastern Arab countries. An 18-year-old Saudi woman presented to the facial plastic clinic of King Fahad Medical City, Riyadh, with a complaint of an additional small left nasal opening since birth. She under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Supernumerary nostril may be associated with other malformations or disease [ 1 , 8 ] According to Franco et al, other congenital malformations were found in 45% of patients with a supernumerary nostril [ 8 ]. The coincident malformations included complete unilateral cleft lip, congenital cataract, esophageal atresia, imperforate anus and patent ductus arteriosus, osteoma of the ethmoid sinus, and congenital adrenal hyper-plasia [ 1 , 8 ]. Choanal atresia can also be associated with other malformations or disease [ 3 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Supernumerary nostril may be associated with other malformations or disease [ 1 , 8 ] According to Franco et al, other congenital malformations were found in 45% of patients with a supernumerary nostril [ 8 ]. The coincident malformations included complete unilateral cleft lip, congenital cataract, esophageal atresia, imperforate anus and patent ductus arteriosus, osteoma of the ethmoid sinus, and congenital adrenal hyper-plasia [ 1 , 8 ]. Choanal atresia can also be associated with other malformations or disease [ 3 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Choanal atresia is an uncommon congenital disorder in which the back of the nasal passage (choana) is blocked, usually by abnormal bony or soft tissue (membranous) due to failed recanalization of the nasal fossae during fetal development [ 1 3 ]. The incidence of congenital choanal atresia is about 1: 5000 to 1: 8000 [ 1 , 2 ]. A supernumerary nostril is a much rarer congenital anomaly with an unknown etiology [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation